Basal Body Protein TbSAF1 Is Required for Microtubule Quartet Anchorage to the Basal Bodies in Trypanosoma brucei - Xiaoduo Dong (American Society for Microbiology, 2020)
ABSTRACT Sperm flagellar protein 1 (Spef1, also known as CLAMP) is a microtubule-associated protein involved in various microtubule-related functions from ciliary motility to polarized cell movement and planar cell polarity. In Trypanosoma brucei, the causative agent of trypanosomiasis, a single Spef1 ortholog (TbSpef1) is associated with a microtubule quartet (MtQ), which is in close association with several single-copied organelles and is required for their coordinated biogenesis during the cell cycle. Here, we investigated the interaction network of TbSpef1 using BioID, a proximity-dependent protein-protein interaction screening method. Characterization of selected candidates provided a molecular description of TbSpef1-MtQ interactions with nearby cytoskeletal structures. Of particular interest, we identified a new basal body protein TbSAF1, which is required for TbSpef1-MtQ anchorage to the basal bodies. The results demonstrate that MtQ-basal body anchorage is critical for the spatial organization of cytoskeletal organelles, as well as the morphology of the membrane-bound flagellar pocket where endocytosis takes place in this parasite. IMPORTANCE Trypanosoma brucei contains a large array of single-copied organelles and structures. Through extensive interorganelle connections, these structures replicate and divide following a strict temporal and spatial order. A microtubule quartet (MtQ) originates from the basal bodies and extends toward the anterior end of the cell, stringing several cytoskeletal structures together along its path. In this study, we examined the interaction network of TbSpef1, the only protein specifically located to the MtQ. We identified an interaction between TbSpef1 and a basal body protein TbSAF1, which is required for MtQ anchorage to the basal bodies. This study thus provides the first molecular description of MtQ association with the basal bodies, since the discovery of this association ∼30 years ago. The results also reveal a general mechanism of the evolutionarily conserved Spef1/CLAMP, which achieves specific cellular functions via their conserved microtubule functions and their diverse molecular interaction networks.